Electromagnetic Vibrational Energy Harvesters: A Review - Andrew Muscat; Soham Bhattacharya; Yong Zhu (Sensors, 2022)
As industries need more real-time monitoring and interconnected systems, the demand for wireless sensors expands. Vibrational energy harvesters are a potential solution for powering these sensors, as vibrations commonly exist where monitoring occurs. Developments in low-power circuitry have also led to the feasibility of these types of harvesters. Electromagnetic harvesters are a standout among various types of vibrational harvesters due to their ability to capture kinetic energy in a low-frequency range. This leads to these devices being more applicable in real-world applications where ambient vibrations are typical of having low frequencies. Hence, extensive research has been undertaken to make electromagnetic harvesters more efficient and compact. This review study aims to examine recent literature that has made advancements and demonstrated the full potential of such devices.